Paul and the mission of the church : Philippians in ancient Jewish context - Ware, James P. (James Patrick), 1957-; Ware, James P. (James Patrick), 1957- (Grand Rapids, Mich. : Baker Academic, 2011)
This essential study examines Paul's letter to the Philippians in its ancient Jewish context, making a convincing case that Paul expected churches to continue the work of spreading the gospel.
pt. 1. Conversion of Gentiles in Ancient Judaism: The problem of Jewish mission ; Conversion of Gentiles in Isaiah and elsewhere in the Hebrew Bible ; Conversion of Gentiles and interpretation of Isaiah in Second Temple Judaism -- pt. 2. Mission in Philippians: The progress of the gospel in Philippians ; Suffering and mission in Philippians ; The mission of the church in Philippians.
Originally published in 2005 by Brill, under the title: The mission of the church in Paul's letter to the Philippians in the context of ancient Judaism (Supplements to Novum Testamentum ; v. 120).
Includes bibliographical references (p. [293]-335) and indexes.
Keywords: Paul, -- the Apostle, Saint; Bible. -- Criticism, interpretation, etc; Bible. -- Criticism, interpretation, etc. -- History; Missions -- Biblical teaching; Mission of the church -- Biblical teaching; Gentiles in the Old Testament; Gentiles in the New Testament; Judaism -- Relations -- Christianity; Christianity and other religions -- Judaism